Structures Congress 2020 : selected papers from the Structures Congress 2020, April 5-8, 2020, St. Louis, Missouri - Soules, James G. 1957- (American Society of Civil Engineers, 2020)
Selected papers from the Structures Congress 2020. This collection contains 70 peer-reviewed papers on a broad array of contemporary issues in structural engineering. Topics include: blast and impact loading and response; bridges, tunnels, and other transportation structures; building; engineering education; forensic investigations of structures; nonbuilding and special structures; and research topics. This proceedings focuses on topics important to practitioners, academics, and researchers at all levels.
Keywords: Structural engineering -- Congresses.; Buildings -- Blast effects -- Congresses.; Loads (Mechanics) -- Congresses.; Bridges -- Design and construction -- Congresses.; Buildings -- Protection -- Congresses.; Earthquake resistant design -- Congresses.; elektronické knihy; electronic books